Dinamika dan Tantangan Pemberdayaan Komunitas Nelayan Pulau Banyak Aceh Singkil - Muhajir Al Fairusy (Jurnal Transformasi Administrasi, 2013)
This paper describes the dynamics of cultural pattern of traditional fisherman working relationship (palawik) with Owner Capital (employer) and the role of government in economic empowerment of fishing communities in the island province of Aceh Singkil District Lots. Through the study of cultural anthropology found that the pattern of relationships between fishermen palawik still stuck in the control of the employer. Then added another goal improper government intervention in economic empowerment. The condition causes palawik fishermen have not reached economic welfare.